Tourism Destination Development in Kapur Ciampea Mountain, Bogor - Rizki Nurul Nugraha; Akbar Tegar Pratama; Muhammad Azfa As-syifa (Westscience Press, 2024)
The research was conducted at Kapur Ciampea Mountain, Bogor on January 1, 2024. The purpose of this research is to find out the application of 3A at Kapur Ciampea Mountain and the development of the tourist destination. The method of analysis in this study is qualitative, with a qualitative descriptive analysis approach and SWOT analysis. The results of the study, the tourist attractions provided are very diverse, the amenity/facilities provided are quite good but there are still some facilities that need to be improved such as parking areas and public toilets, access to transportation is the advantage of this destination, the condition of the road to the destination is quite good, and access to information still needs to be improved, especially in access to digital information. To overcome these problems, the right strategy to develop Kapur Ciampea Mountain is to take advantage of the potential of website development and personal social media, improve inadequate facilities, training to staff and collaboration with influencers or community leaders, build a comprehensive disaster mitigation plan, carry out environmental restoration activities, and focus on improving the quality of services and nature education programs to overcome threats and risks that may occur.